2011
DOI: 10.1016/j.socscimed.2011.02.022
|View full text |Cite
|
Sign up to set email alerts
|

The limits of resilience: Distress following chronic political violence among Palestinians

Abstract: We examined posttraumatic stress disorder (PTSD) and depression symptom trajectories during ongoing exposure to political violence, seeking to identify psychologically resilient individuals and the factors that predict resilience. Face-to-face interviews were conducted with a random sample of 1196 Palestinian adult residents of the West Bank, Gaza, and East Jerusalem across three occasions, six months apart (September, 2007–November,2008). Latent growth mixture modeling identified PTSD, and depression symptom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
110
3
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(128 citation statements)
references
References 40 publications
7
110
3
8
Order By: Relevance
“…Findings are less in number but more consistent across studies; for instance, three separate studies each found older adults fared better than younger adults in the face of political violence (Hobfoll, Mancini, Hall, Canetti, & Bonanno, 2011;Khamis, 1998b;Kimhi, 2010).…”
Section: Adultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Findings are less in number but more consistent across studies; for instance, three separate studies each found older adults fared better than younger adults in the face of political violence (Hobfoll, Mancini, Hall, Canetti, & Bonanno, 2011;Khamis, 1998b;Kimhi, 2010).…”
Section: Adultsmentioning
confidence: 95%
“…Women's educational level might also offer some degree of psychological protection from the effects of political violence (Khamis, 1998b). In addition, several studies found that males demonstrated more resilience than females (Hobfoll, et al, 2011;Kimhi, 2010).…”
Section: Adultsmentioning
confidence: 99%
“…This social support can come in a variety of forms, such as parents (Masten et al 2004), friends (Kiang et al 2010;Hobfoll et al 2011), social networks, institutions, and positive role models (Werner and Smith 1992).…”
Section: Risks As Sources Of Mental Stress and Traumamentioning
confidence: 99%
“…self-esteem, social skills, job skills) and energy resources (i.e. food, money, credit, knowledge) (Hobfoll, 1998:54;Hobfoll, Mancini, Hall, Canetti & Bonanno, 2011:1402. The loss of resources in a family system is experienced like a downward spiral of losses which leaves the family system feeling hopeless and out of control.…”
Section: Loss Of Resourcesmentioning
confidence: 99%